ISOLASI DAN UJI AKTIVITAS ANTIBAKTERI ISOLAT FUNGI ENDOFIT AKAR TUMBUHAN CEMBA (Acacia rugata (Lam.) fawc. Rendle) - Ismail Ismail (STIFA Makassar, 2022)
Cemba (Acacia rugata (Lam.) Fawc. Rendle) is a plant endemic to South Sulawesi, especially in the Enrekang regency, has a chemical content including essential oils, flavonoids, saponins, terpenoids, steroids and alkaloids and has antibacterial properties. This study aimed to isolate endophytic fungi from the roots of the cemba plant (Acacia rugata (Lam.) Fawc. Rendle) which have the potential to produce candidate antibacterial compounds tested against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 83125. Steps in this study included the isolation of endophytic fungi. , purification, antagonist test. The results of this study allowed to obtain 3 isolates of endophytic fungi resulting from the isolation process which have different characteristics and have potential as antibacterial with strong and very strong inhibition against E.coli ATCC 83125 and S. aureus ATCC 25923.